INNOVATIVE TEACHING TECHNIQUES COLLABORATIVELY IMPLEMENTED IN WRITING CLASSES BY PRE-SERVICE - I Nyoman Suparsa; Ida Bagus Nyoman Mantra; I Nengah Astawa; Ida Ayu Made Sri Widiastuti; Ni Luh Sukandi (International Journal of Applied Science and Sustainable Development (IJASSD), 2021)
This collaborative research was aimed at exploring teaching strategies used in teaching writing by pre-service teachers who conducted practice teaching junior high schools in Denpasar. The research was done due to the problems faced by the teachers in teaching writing. Some innovative techniques were practiced by pre-service teachers to overcome the problems. The innovative techniques proposed were clustering technique, roundtable technique, think pair share, and mind mapping. It was believed that these techniques would be able to improve the students’ ability in writing. After the implementation of the teaching strategies, it was revealed that all techniques offered were able to foster the students’ ability in writing. Therefore, the study implies that innovative learning strategies should be implemented in every teaching activity, especially in teaching writing.